Falsified and substandard medicines trafficking: A wakeup call for the African continent - Yusuf Hassan Wada; Abdullahi Abdulrahman; Musabu Ibrahim Muhammad; Vivian Chiemerie Owanta; Pearl Udoka Chimelumeze; Garba M. Khalid (Elsevier, 2022)
While great effort is being placed on reducing disease burdens in Africa, the circulation of falsified and substandard medicines in the continent are reversing the hard-won gains. This commentary provides insights on the high (and increasing) burden, impact and threat that falsified and substandard medicines pose to the region's development. The proposed recommendations, such as a coherent multi-sectorial and government-led strategy, call for a fundamental rethink of approaches towards strong regulations, policies, legislations, community-based approaches, collaborations and investments, which all must be scaled up before this the situation gets out of control. These recommendations are of paramount importance and have the potential to ensure access to genuine medicines and also to avert therapeutic failure and intoxication from dangerous substances. In addition, there will be added benefits to the economic, social, health and well-being of the region. Concerted efforts towards medicine regulations have enormous potential to contribute towards averting many preventable deaths and reducing disease burden in the region. A paradigm shift is necessary to ensure quality medicines reach patients at community and healthcare facilities to prevent this silent epidemic in Africa.